Teachers' Perceptions Using Narrative for Teaching English for Young Learners - Rani Evita Sari; Dina Merris Maya Sari (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2022)
This article examines the use of narrative as a learning method in English classes for young learners. This study used descriptive qualitative method. It examines the teacher's perspective in using narrative in lesson plans. Interviews were conducted with both novice and experienced teachers in teaching young learners about their preferences and experiences when using narrative-based learning. Research results show that teachers assume narrative-based lessons are very time-consuming so it is not easy to use narratives in learning, so narratives also have a positive impact on the theoretical part could be seen on students and for teaching, 5 out of 7 teachers think coursebooks are not enough for narrative-based learning so they use other sources such as internet and storybooks.